Case Report: Ventriculoperitoneal Shunt Catheter Migration and Transanal Extrusion in Persistent Vegetative State Adult Patient - Fauzi, Asra Al; Parenrengi, Muhammad Arifin; Wahyuhadi, Joni; Subagio, Eko Agus; Turchan, Agus (Folia Medica Indonesiana, 2019)
Hyaluronic acid (HA) is a glycosaminoglycan with a straight-chain polymer arrangement defined as the extracellular matrix constituent. High molecular weight HA has normal physicochemical, biological, and physiological properties whereas low molecular weight has the property of angiogenesis, inflammation, and suppresses apoptosis. This study occupied the samples of 35 paraffin block from poorly and well differentiated retinoblastoma tissue and 8 normal retinal block which have been collected for 4 years from 2010-2013 at Dr. Soetomo Hospital, Surabaya, Indonesia. Afterwards, the paraffin blocks were immunohistochemically examined for HA staining, expression of cell proliferation (Ki-67), and cell apoptosis to determine intratumoral aggressiveness of retinoblastoma. HA on poorly differentiated retinoblastoma stain with a high immunostaining of 76.2%, while well differentiated retinoblastoma on the highest HA staining was revealed to be at moderate level of 64.3%, and not appear in normal retina. In poorly differentiated retinoblastoma, the location of most HA stain is in the cell cytoplasm (87.5%). In the well differentiated retinoblastoma, the HA immunostaning mainly occurred in the cell membrane (73.7%). Histopathological retinoblastoma grading showed a significant correlation (p <0.01) towards several variables of HA immunostaining, Ki-67, and cell apoptosis. In addition, the histopathological retinoblastoma grading also revealed a significant correlation (p <0.01) towards the location of HA staining (cell membrane and cytoplasm). Both stainings are also play role in retinoblastoma differentiation. The malignancy of retinoblastoma can be proven by the increased HA staining at cytoplasm in poorly differentiated and associated with increased of cell proliferation along with decreased apoptosis.